Using Rubber Aggregate Derived from Discarded Tires for Producing Cement Concrete towards Resource Recovery and Environmental Protection in Vietnam - Luong, Nguyen Duc; Long, Hoang Vinh; Tuan, Ngo Kim; Thai, Nguyen Duy (International Journal of Sustainable Energy and Environmental Research, 2017)
This study aims to explore the possibility to use rubber particles derived from discarded tire as aggregates for replacing fine and coarse natural aggregates to produce cement concrete towards resource recovery and environmental protection in Vietnam. The experimental results showed that the workability of fresh rubberized concrete was improved when replacing natural fine aggregate (sand) with fine rubber particles (2.5-5 mm) at the replacing proportions of 30-50% by volume, and when replacing natural coarse aggregate (crushed stone) with coarse rubber particles (5-20 mm) at the replacing proportions of 10-30% by volume. With respect to the mechanical properties of hardened rubberized concrete, a larger reduction in the compressive and flexural strengths was generally found when the replacing proportions increased and when coarse aggregate rather than fine aggregate was replaced by rubber particles at all replacing proportions. However, the study results also indicated that using fine rubber particles for replacing fine natural aggregate at the low replacing proportion (up to 10%) might not cause the significant effect on the compressive and flexural strength of rubberized concrete.